RENAL TUBERCULOSIS: AN INCIDENTAL FINDING IN TYPE II DIABETES - Sulaiman MM; Bakki B; Bathnna SJ; Omoaghe C; Sanni IO; Shettima J (Ntec Specialist, 2018)
Background: Renal tuberculosis constitutes 14% to 41% of cases of extrapulmonary TB and with HIV pandemic; its prevalence is expected to increase. Case report: We report a case of a 51-year-old diabetic/hypertensive female admitted via the A and E with complaints of vomiting and generalized malaise. She had hyponatraemia of 119mmol/l, creatinine 687µmol/L, and urea 28mmol/L. Her kidneys were normal sized and echogenic on ultrasound examination. She was treated for hyponatraemia with normal saline and discharged. She reported at the clinic 2 weeks later with complaints of fever, back pain and right sided neck swelling. Neck ultrasound revealed cystic mass in the lower part of the sternomastoid muscle, Xrays were normal, Urinary AFB done on four urine specimen collected over days was negative and Mantoux test was reactive. Spinal examination was unremarkable except for presence of tenderness at the T6 to T7 vertebrae. A diagnosis of extra pulmonary TB involving the cervical lymph nodes and spine was made and she was commenced on quadruple anti TB drugs which resulted in improvement of her renal function. Conclusion: The diagnosis of renal tuberculosis is usually difficult due to low yield of laboratory tests such as urine microscopy for AFB. High index of suspicion is often required in most patients